Análises de agrupamento dos valores genéticos para produção de leite e persistência da lactação em bovinos da raça Guzerá - da Cruz, Diego Augusto Campos; Savegnago, Rodrigo Pelicioni [UNESP]; Santana, Annaíza Braga Bignardi; Peixoto, Maria Gabriela Campolina Diniz; Bruneli, Frank Angelo Tomita; Faro, Lenira El (FapUNIFESP (SciELO), 2016)
The aim of this study was to explore the pattern of genetic lactation curves of Guzerá cattle using cluster analysis. Test-day milk yields of 5,274 first-lactation Guzerá cows were recorded in a progeny test. A total of 34,193 monthly records were analyzed with a random regression animal model using Legendre polynomials to fit additive genetic and permanent environmental random effects and mean trends. Hierarchical and non-hierarchical cluster analyses were performed based on the EBVs for monthly test-day milk yield, peak yield, lactation persistency, and partial cumulative and 305-day yields. The heritability estimates for test- day milk yields ranged from 0.24 to 0.52. Cluster analysis identified animals in the population that belong to different groups according to milk production level and lactation persistency.
Cluster analysis of breeding values for milk yield and lactation persistency in guzerá cattle
Keywords: Breeding values; Lactation curve; Random regression